Traditional Self-Reported Dietary Instruments Are Prone to Inaccuracies and New Approaches Are Needed - Ravelli, Michele N.; Schoeller, Dale A. (Frontiers in Nutrition, 2020)
Background: Diet is a modifiable behavior that influences an individual’s health. Because of this, diet assessment is an important component of public health surveillance, evaluating response to community health interventions, and monitoring individual compliance to medical interventions. Diet assessments are usually performed using one of three basic methods: diet recall, diet diaries, or food-frequency questionnaires. Although these three assessment instruments have displayed strong agreement between themselves, when reported intake is compared with intake measured using quantitative nutrient biomarkers, investigators have identified systematic misreporting errors for all three of these self-reported dietary instruments. Aims: Summarize the state of knowledge regarding misreporting, why it impedes diet-health research, and introduce advances in the collection and treatment of dietary data. Methods: Review and summarize published data on misreporting and recent efforts to reduce such errors. Results: The evidence demonstrates strong and consistent systematic underreporting of EIn across adults and children studies. Underreporting of EIn has been found to increase with body mass index (BMI) and differences between macronutrient reports indicatethat not all foods are underreported equally. Protein is least underreported, but which specific foods are commonly underreported are not known. Conclusions: Because energy underreporting varies as a function of BMI, self-reported EIn should not be used for the study of energy balance in the study of obesity. The between-individual variability in the underreporting of self-reported intake of energy and other nutrients attenuates diet-disease relationships. Recent efforts to correct for underreporting have reduced misreporting of diet outcomes, but improvements have been incremental in nature and more research is needed to validate and extend these efforts.